Glucose regulates cotton fiber elongation by interacting with brassinosteroid. (12th October 2021) - Li, Xinyang; Liu, Wei; Ren, Zhongying; Wang, Xingxing; Liu, Ji; Yang, Zuoren; Zhao, Junjie; Pei, Xiaoyu; Liu, Yangai; He, Kunlun; Zhang, Fei; Zhang, Zhiqiang; et al.
Abstract : Cotton fiber length is an important index of quality, which is affected by many factors. We identify glucose as acting as a key mediator during cotton fiber elongation through interaction with brassinosteroid. Abstract: In plants, glucose (Glc) plays important roles, as a nutrient and signal molecule, in the regulation of growth and development. However, the function of Glc in fiber development of upland cotton ( Gossypium hirsutum ) is unclear. Here, using gas chromatography-mass spectrometry (GC-MS), we found that the Glc content in fibers was higher than that in ovules during the fiber elongation stage. In vitro ovule culture revealed that lower Glc concentrations promoted cotton fiber elongation, while higher concentrations had inhibitory effects. The hexokinase inhibitor N -acetylglucosamine (NAG) inhibited cotton fiber elongation in the cultured ovules, indicating that Glc-mediated fiber elongation depends on the Glc signal transduced by hexokinase. RNA sequencing (RNA-seq) analysis and hormone content detection showed that 150mM Glc significantly activated brassinosteroid (BR) biosynthesis, and the expression of signaling-related genes was also increased, which promoted fiber elongation. In vitro ovule culture clarified that BR induced cotton fiber elongation in a dose-dependent manner. In hormone recovery experiments, only BR compensated for the inhibitory effects of NAG on fiber elongation in a Glc-containing medium. However, the ovules cultured with the BR biosynthetic inhibitor brassinazole and from the BR-deficient cotton mutant pag1 had greatly reduced fiber elongation at all the Glc concentrations tested. This demonstrates that Glc does not compensate for the inhibition of fiber elongation caused by BR biosynthetic defects, suggesting that the BR signaling pathway works downstream of Glc during cotton fiber elongation. Altogether, our study showed that Glc plays an important role in cotton fibre elongation, and crosstalk occurs between Glc and BR signaling during modulation of fiber elongation.